Modern Anti-Semitism in the Czech Lands between the Years 1895–1989: A Comparison of the Main Stages of the Most Influential Parts of Czech Nationalism - Soukupová, Blanka (Lidé města, 2011)
This study specifies and characterizes the phases of modern Czech anti-Semitism, which it defines as a range of mutually interdependent anti-Jewish manifestations. In each of these phases (anti-Semitism in Austro-Hungary, in the First Republic, in the Second Republic, during the Protectorate and after World War II) it analyzes not only specific manifestations of escalating Czech nationalism, but especially the social functions of anti-Semitism.